Draft of the basic systematization of inorganic and organic macromolecular compounds - Čatić, Igor; Barić, Gordana; Galić, Kata; Grancarić, Anamarija; Rogić, Ana Rujnić- Sokele, Maja; Karavanić, Ivor (2011)
The word polymers is usually related to plastics and rubber. This definition narrows down the meaning of the word to a very significant group of materials, but leaves out numerous other substances and materials that are also polymers. The consequence is the difficulty in observing the interconnection or comparability of polymers among each other or with other non-polymeric substances and materials. Therefore, a draft of the basic systematization of inorganic and organic macromolecular compounds has been elaborated.
Projekt MZOS
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG